Remodeling of left ventricle in hypertensive patients with renal addition arteries: associations with renin level and glomerular filtration rate - Yu. P. Red’ko; N. N. Gladkikh; A. V. Yagoda (Лечащий Врач)
The article is devoted to analysis of relationship of left ventricular remodeling, plasma renin level, glomerular filtration rate in patients with arterial hypertension and renal additional arteries. It is shown that hormonal and hemodynamic factors in young patients with arterial hypertension of 1–2 degrees with renal additional arteries create a load on left ventricle, contributing to pathological myocardial remodeling in the form of eccentric hypertrophy and concentric remodeling.